Pengembangan Bahan Ajar berbasis Socio-Scientific Issues untuk Meningkatkan Higher Order Thinking Skill - Reza Kharisma Siswi Laksono*; Yuni Wibowo (Universitas Syiah Kuala, 2022)
To improve the learning quality, required strategies by develop the teaching materials using the socio-scientific issues (SSI) model. In this study, teaching materials were developed through a reconstruction process and context in real life through SSI. One issue that very close to the context of real life is the problem of cupping the circulatory system. The use of SSI as a context is expected to be used as a link to real problems in the community. The purpose of this study was to determine the characteristics, quality, and learning materials for students based on SSI. The material contains about the circulatory system which contains the pros and cons of problems in the community regarding cupping. This research was conducted by applying RD with ADDIE (analyze, design, development, implementation, and evaluation) model, but is limited to the development stage. Research subjects in the limited product trial were conducted on a biology subject teacher and 30 students of class XI MIPA 1 SMAN 1 Piyungan. The results indicate the teaching materials developed have the characteristics of SSI-based teaching materials so that they are related to problems related to the human circulatory system and can be used as a complement to other teaching materials. This teaching material invites students to take an attitude regarding the pros and cons of cupping in the community. As a product, the textbooks have good quality and suitable for SSI-based teaching materials based on aspects of the suitability of the material, presentation, language, appearance and student responses